2021
DOI: 10.1021/acsomega.1c00252
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Geochemical Significance of Rearranged Hopanes in Jurassic Source Rocks and Related Oils in the Center of the Sichuan Basin, China

Abstract: Gas chromatography-mass spectrometry (GC-MS) analysis has revealed extremely high abundances of rearranged hopanes in Jurassic source rocks and related crude oils in the center of the Sichuan Basin. The detected rearranged hopanes include 17α(H)-diahopanes (C 27 D and C 29−35 D), early-eluting rearranged hopanes (C 27 E and C 29−33 E), and 18α(H)-neohopanes (C 29 Ts and Ts). Both the 17α(H)-diahopanes and the early-eluting rearranged hopanes exhibit a distribution pattern similar to that of the 17α(H)-hopane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The light hydrocarbon parameters and carbon isotope composition indicate that Family I oils are derived from source rocks dominated by sapropelic kerogen. In previous studies, oils from the Da'anzhai Member and Lianggaoshan Formation in the study area were demonstrated to be self-sourced by dark lacustrine mudstones within these units (Lu et al, 2021). Family I oils are therefore likely to be derived from source rocks in the Da'anzhai Member and Lianggaoshan Formation.…”
Section: Statistical Groupingmentioning
confidence: 80%
See 1 more Smart Citation
“…The light hydrocarbon parameters and carbon isotope composition indicate that Family I oils are derived from source rocks dominated by sapropelic kerogen. In previous studies, oils from the Da'anzhai Member and Lianggaoshan Formation in the study area were demonstrated to be self-sourced by dark lacustrine mudstones within these units (Lu et al, 2021). Family I oils are therefore likely to be derived from source rocks in the Da'anzhai Member and Lianggaoshan Formation.…”
Section: Statistical Groupingmentioning
confidence: 80%
“…The tight Lianggaoshan Formation reservoir is likewise self-sourced by similar OM-rich dark mudstones (Chen et al, 2014;Chen et al, 2015;. In addition, the shale source rocks in these two units have generated the light oils which are reservoired in the Middle Jurassic First Member of the Shaximiao Formation (Li et al, 2017;Lu et al, 2021). Recent exploration efforts in the Qiulin and Bajiaochang areas near to the Gongshanmiao and Jinhua oilfields in the centre of the Sichuan Basin have led to the discovery of tight oils in the overlying Second Member of this formation (J 2 s 2 ) (Huang et al, 2021), although the origin of this oil remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Complex blends of high molecular weight aliphatic hydrocarbons with branched and/or cyclic structure (e.g., steranes and hopanes) are the bulk of petrol industry products, like fuels and solvents, and affect the exhausts (Xiao et al 2019;Lu et al 2021), soils and sediments (Arfaoui 2014). Their identification and quantification, combined with the ratio rates of burdens of subgroups, has revealed that composition depends on oil maturity or on progress of oxidative/biological attack of original blend (Lobodin et al 2016;Volkman et al 1997;Simoneit 1999).…”
Section: Branched and Cyclic Hydrocarbonsmentioning
confidence: 99%
“…(c) Correlation of the Cretaceous strata in the northwestern and western Sichuan Basin. Reprinted from ref ( 33 ). Copyright 2021 American Chemical Society.…”
Section: Introductionmentioning
confidence: 99%